EFFECT OF POSTOPERATIVE ANALGESIA AFTER PRE-INCISIONAL LOCAL INFILTRATION WITH LEVOBUPIVACAINE IN LAPAROSCOPIC CHOLECYSTECTOMY (Journal of Medical & Health Sciences Review, 2025)
Background: Postoperative pain following laparoscopic cholecystectomy remains a significant cause of discomfort and delayed recovery despite the minimally invasive approach. Pre-incisional local infiltration with long-acting local anesthetics such as levobupivacaine has been proposed as an effective strategy for postoperative pain control and opioid-sparing analgesia.Objective: To evaluate the effect of pre-incisional local infiltration with levobupivacaine on postoperative pain intensity, analgesic requirements, and patient satisfaction following laparoscopic cholecystectomy.Methods: This prospective, randomized, controlled study included 100 patients undergoing elective laparoscopic cholecystectomy. Participants were divided into two equal groups: Group A received pre-incisional infiltration with 0.25% levobupivacaine, while Group B (control) received an equal volume of normal saline. Pain intensity was assessed using the Visual Analogue Scale (VAS) at 2, 6, 12, and 24 hours postoperatively. Total analgesic consumption and patient satisfaction scores were also recorded and statistically analyzed using SPSS version 25.Results: Patients in the levobupivacaine group demonstrated significantly lower mean VAS scores at 2, 6, and 12 hours postoperatively (p < 0.001). The total requirement for rescue analgesia was markedly reduced compared with the control group (p < 0.01). Patient satisfaction was notably higher among those receiving levobupivacaine infiltrations, and no adverse events were reported.Conclusion: Pre-incisional local infiltration with levobupivacaine provides effective postoperative analgesia, reduces analgesic consumption, and enhances patient comfort following laparoscopic cholecystectomy. Its safety, simplicity, and opioid-sparing benefits make it a valuable component of multimodal analgesia and Enhanced Recovery After Surgery (ERAS) protocols.